2017
DOI: 10.1371/journal.pone.0184221
|View full text |Cite
|
Sign up to set email alerts
|

High-level dietary cadmium exposure is associated with global DNA hypermethylation in the gastropod hepatopancreas

Abstract: 5-methylcytosine (5mC) is a key epigenetic mark which influences gene expression and phenotype. In vertebrates, this epigenetic mark is sensitive to Cd exposure, but there is no information linking such an event with changes in global 5mC levels in terrestrial gastropods despite their importance as excellentecotoxicological bioindicators of metal contamination. Therefore, we first evaluated total 5mC content in DNA of the hepatopancreas of adult Cantareus aspersus with the aim to determine whether this epigene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
34
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 58 publications
9
34
2
Order By: Relevance
“…1). The measured values in controls were within the same range with those assessed in one of our previous experiments [1], as well as with those determined in specimens sampled from unpolluted areas [15,16]. The maximum Cd levels observed here are also of interest from an ecotoxicological point of view since they are among the highest values ever reported in C. aspersus.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…1). The measured values in controls were within the same range with those assessed in one of our previous experiments [1], as well as with those determined in specimens sampled from unpolluted areas [15,16]. The maximum Cd levels observed here are also of interest from an ecotoxicological point of view since they are among the highest values ever reported in C. aspersus.…”
Section: Resultssupporting
confidence: 89%
“…In a previous study, were investigated the retention of Cd in adult C. aspersus snails at similar exposure doses, but for shorter durations, namely 14, 28 and 56 days. Interestingly, the dose from which significant increases in hepatopancreas Cd were detected was similar [1].These results suggest the potential existence of threshold level below which these land snails are able to maintain relatively stable cadmium concentrations in the hepatopancreas, which is up to 5 mg/kg d. wt.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…Additionally, this study demonstrated the presence of a relationship between DNA methylation and multigenerational effects, with DNA methylation decreasing with increasing prednisolone concentration in the F1 (Bal et al 2017). Furthermore, metals such as cadmium have been shown to induce DNA methylation in terrestrial snails, although minimal literature exists linking DNA methylation caused by metal exposure with multigenerational effects (Nica et al 2017).…”
Section: Multigenerational Ecotoxicological Studiesmentioning
confidence: 75%